Використання поведінкової моделі Фогга для навчання з питань інформаційної безпеки - Божко, О. В. (ХНУРЕ, 2023)
То configure the network of optical-electronic stations, it is necessary to take into account the features of wireless communication modules. EBYTE E32- 433T20DT modules have 2 communication modes (data transmission with a fixed address and destination channel, or broadcast data transmission) and 4 operation modes (normal operation mode, wake-up mode, sleep mode with hibernation, and sleep mode with reduced power consumption). The operating modes are set using variable parameters M0 and M l. In normal mode, the module receives data from the UART or wireless interface, it is possible to transmit data in packet mode up to 58 bytes in size. The wake-up mode allows you to automatically add a preamble to the transmitted packet.